Food additive sodium bisulfite induces intracellular imbalance of biothiols levels in NCM460 colonic cells to trigger intestinal inflammation in mice. (15th April 2022) - Wu, Wei; Fu, Gaoqing; Xuan, Rongrong; Zhai, Leilei; Lu, Yujia; Tang, Min; Liu, Jingwangwei; Zhang, Chundan; Chen, Haimin; Wang, Feng
Highlights: Excessive NaHSO3 induces imbalance of biothiols levels in the NCM460 cells and mice. NaHSO3 exerts proinflammatory effects by promoting ROS-mediated NF-κB pathway. Vitamin B6 supplementation can improve NaHSO3 -induced colon injury in the Balb/c mice. Abstract: Sulfites and other preservatives are considered food additives to prevent pathogen growth in food, and they are generally regarded as safe since the late 1950s. However, the possible effects of sulfites on potential damage to host intestinal tissue remain largely unexplored. Given that endogenous sulfite mainly comes from the metabolism of biothiol, we attempted to clarify the relationship among biothiol levels, gut and food additives sulfite, including sodium bisulfite (NaHSO3 ), and the possible mechanism of sulfite affecting the intestine. In the present study, the NaHSO3 treatments markedly increased the homocysteine (Hcy) level but decreased the cysteine (Cys) level by promoting the expression of Hcy synthase and inhibiting the activities of cystathionine β-synthase and cystathionine γ-lyase in NCM460 cells. The level of methionine (Met) was not significantly changed, but NaHSO3 promoted ROS-mediated NF-κB signaling pathway, and increased the expressions of proinflammatory cytokines by regulating the levels of Hcy and Cys in NCM460 cells. Vitamin B6 (VB6 ) supplementation successfully ameliorated NaHSO3 -induced damage in NCM460 cells and the colon of Balb/c mice. Altogether, our study provided valuable insights into the safety evaluation of food preservatives. Besides, VB6 could be used as a promising candidate in novel therapies for sodium bisulfite-induced intestinal inflammation.